Cultural Practices for Vegetable and Small Fruit Crops: Does Shoot Pruning Improve Tomato Yield and Reduce Bacterial Spot Infestation? - Bielinski M. Santos; Gary E. Vallad (EDIS)
HS1180, a 4-page illustrated fact sheet by Bielinski M. Santos and Gary E. Vallad, examines the effectiveness of shoot pruning to control bacterial spot infestation and improve yield of tomato. Published by the UF Department of Horticultural Sciences, July 2010.